Comparing Semantic Fluency in American Sign Language and English - Sehyr, Zed Sevcikova (J Deaf Stud Deaf Educ, 2018)
This study investigated the impact of language modality and age of acquisition on semantic fluency in American Sign Language (ASL) and English. Experiment 1 compared semantic fluency performance (e.g., name as many animals as possible in 1 min) for deaf native and early ASL signers and hearing monolingual English speakers. The results showed similar fluency scores in both modalities when fingerspelled responses were included for ASL. Experiment 2 compared ASL and English fluency scores in hearing native and late ASL–English bilinguals. Semantic fluency scores were higher in English (the dominant language) than ASL (the non-dominant language), regardless of age of ASL acquisition. Fingerspelling was relatively common in all groups of signers and was used primarily for low-frequency items. We conclude that semantic fluency is sensitive to language dominance and that performance can be compared across the spoken and signed modality, but fingerspelled responses should be included in ASL fluency scores.